Menelusuri Paradigma Politik Kebangsaan Nahdlatul Ulama (NU) dalam Konteks Bernegara - Muhammad Ullin Nuha; Hidayatul Maslakha (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2024)
Thel aim of this research is to reflect further on thel national political paradigm of NUl as one of the thel largest social organizations in Indonesia. Thel national political paradigm of NUl must continue to be in harmony and line with thel basic principles of Ahlulssulnnah Wal Jama'ah. Thel approach to this research is qualitative and thel type uses library research research methods using literature (libraries). Thel results of this research are that thel ideal framework of NUl as a jahiliyyah diniyah ijtima'iyyah (religious and social organization) must bel strengthened to prevent religious organizations from being weakened by practical political desires that can weaken them. This spirit and strategy can bel used not only by Nahdlatull Ullama, but also by other Islamic organizations that continue to fight for their position in thel national community. In this way, sociopolitical articulation as jam'iyyah diniyah ijtima'iyyah will develop paradigmatically.